2005
DOI: 10.1002/lt.20343
|View full text |Cite
|
Sign up to set email alerts
|

Compression of the brachial plexus during right lobe liver donation as a cause of brachial plexus injury: A case report

Abstract: We present a case of brachial plexus injury in a living-related liver donor, most likely caused by compression of the plexus between the 1st rib and clavicle, the result of rib retraction for surgical exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Even with careful positioning and regular monitoring, a wide range and severity of nerve involvement has been observed in clinical practice. Dulitz et al26 reported brachial plexus injury in a living related liver donor possibly due to compression of the plexus between the first rib and clavicle as the result of upward surgical retraction of the rib cage. Surgical complications were also observed, although their occurrence was somewhat less than has been reported 14, 27…”
Section: Discussionmentioning
confidence: 99%
“…Even with careful positioning and regular monitoring, a wide range and severity of nerve involvement has been observed in clinical practice. Dulitz et al26 reported brachial plexus injury in a living related liver donor possibly due to compression of the plexus between the first rib and clavicle as the result of upward surgical retraction of the rib cage. Surgical complications were also observed, although their occurrence was somewhat less than has been reported 14, 27…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that these neuropathies were probably related to prolonged anesthesia, invasive central venous monitoring catheters, and surgical procedures such as venovenous bypass. Another case report noted brachial plexus injury caused by compression of the plexus between the fi rst rib and clavicle, resulting from rib cage retraction for surgical exposure [8].…”
Section: Discussionmentioning
confidence: 99%
“…12,13 To achieve adequate surgical exposure during liver surgery, metal retractors that pull the rib cage in an anterior and cephalad direction are frequently used. 3 In this study, the extent of retraction was routinely monitored by using the loss or dampening of a right radial arterial waveline pressure tracing as a surrogate of compression of the neurovascular bundle between the clavicle and first rib because of retractor use. Interestingly, we found that 82% of neuropathies were left sided, suggesting that attention should also be placed toward the leftward pull of retractors for exposure.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Operative factors unique to major liver surgery may place these patients at particularly increased risk of peripheral nerve injury, such as the routine use of large bore venous catheters, veno-veno bypass, lengthy operative times, potential for significant intraoperative hypotension, and retractors that cause the cephalad displacement of the rib cage toward the clavicle thus compressing the brachial plexus. 3 Although anecdotally described, the incidence of peripheral nerve injury in liver transplantation has not been well investigated. Perhaps, the largest series is in the living donor liver population, the Adult-to-Adult Living Donor Liver Transplantation or A2ALL cohort, in which neuropraxia is reported in 3%-4% of living donors, taking up to 3 y to resolve, and resulting in permanent work disability in some.…”
Section: Introductionmentioning
confidence: 99%